2013
DOI: 10.1073/pnas.1219555110
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened glycolysis under hypoxia supports tumor symbiosis and hexosamine biosynthesis in pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma is one of the most intractable and fatal cancer. The decreased blood vessel density displayed by this tumor not only favors its resistance to chemotherapy but also participates in its aggressiveness due to the consequent high degree of hypoxia. It is indeed clear that hypoxia promotes selective pressure on malignant cells that must develop adaptive metabolic responses to reach their energetic and biosynthetic demands. Here, using a well-defined mouse model of pancreatic cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
351
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 348 publications
(363 citation statements)
references
References 30 publications
8
351
0
4
Order By: Relevance
“…Cell lines were developed from tumors of TAp73 WT and TAp73 knockout mice as previously described. 59 Cells were cultured in DMEM/F-12 (Life Technologies, Saint-Aubin, France), 1.22 mg/ml nicotinamide (Sigma-Aldrich, Lille-Lezennes, France), 5 mg/ml glucose (Sigma-Aldrich), 5% ITS+ (BD Biosciences, Le pont de Claix, France), 100 μg/ml gentamicin (Life Technologies), 1x fungizone (Life Technologies), 5% Nu-serum IV (BD Biosciences), 25 μg/ml BPE (Life Technologies), 20 ng/ml EGF (BD Biosciences), 50 nM 3,3′,5-triiodo-Lthyronine (Sigma-Aldrich), 1 μg dexamethasone (Sigma-Aldrich), and 100 ng/ml cholera toxin (Sigma-Aldrich). After 10 passages, cell culture medium was replaced by DMEM (Life Technologies) supplemented with 10% FBS (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines were developed from tumors of TAp73 WT and TAp73 knockout mice as previously described. 59 Cells were cultured in DMEM/F-12 (Life Technologies, Saint-Aubin, France), 1.22 mg/ml nicotinamide (Sigma-Aldrich, Lille-Lezennes, France), 5 mg/ml glucose (Sigma-Aldrich), 5% ITS+ (BD Biosciences, Le pont de Claix, France), 100 μg/ml gentamicin (Life Technologies), 1x fungizone (Life Technologies), 5% Nu-serum IV (BD Biosciences), 25 μg/ml BPE (Life Technologies), 20 ng/ml EGF (BD Biosciences), 50 nM 3,3′,5-triiodo-Lthyronine (Sigma-Aldrich), 1 μg dexamethasone (Sigma-Aldrich), and 100 ng/ml cholera toxin (Sigma-Aldrich). After 10 passages, cell culture medium was replaced by DMEM (Life Technologies) supplemented with 10% FBS (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, glycolytic genes are often overexpressed in tumor cells (Daskalow et al, 2009;Wolf et al, 2011;Zhou et al, 2011). High rates of glycolysis and the activation of the hexosamine biosynthetic pathway may favor cancer cell survival and aggressiveness (Guillaumond et al, 2013). In the current study, TPI1, PGK1 and beta-enolase enzymes, which are all components of the glycolytic pathway, were up-regulated in MDV-infected chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing increase in lactate released by hypoxic cells serves as an energy source for the neighboring oxygenated cells. 4 This illustrates that these 2 tumor cell populations function symbiotically. Under hypoxic stress, pancreatic cancer cells also show an intense appetite for glutamine, and the resulting enhanced glutaminolysis, coupled with increased glycolytic flux, promotes overactivation of the hexosamine biosynthetic pathway (HBP).…”
mentioning
confidence: 94%
“…In this GEMM, faithfully reproducing the evolution and malignancy of human disease (Pdx1-Cre; LSL-Kras G12D ; Ink4a/Arf fl/fl mice), we have shown that a fifth of the total tumor area is composed of hypoxic cancer cells. 4 The presence of these hypoxic areas creates a glycolytic gradient within the tumor mass, with hypoxic tumor cells exhibiting a higher glycolytic rate than normoxic cells. The ensuing increase in lactate released by hypoxic cells serves as an energy source for the neighboring oxygenated cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation